Electron-volt neutron spectroscopy: beyond fundamental systems. Issue 1 (2nd January 2017) - Andreani, Carla; Krzystyniak, Maciej; Romanelli, Giovanni; Senesi, Roberto; Fernandez-Alonso, Felix
Abstract : This work provides an up-to-date account of the use of electron-volt neutron spectroscopy in materials research. This is a growing area of neutron science, capitalising upon the unique insights provided by epithermal neutrons on the behaviour and properties of an increasing number of complex materials. As such, the present work builds upon the aims and scope of a previous contribution to this journal back in 2005, whose primary focus was on a detailed description of the theoretical foundations of the technique and their application to fundamental systems [see Andreani et al., Adv. Phys. 54 (2005) p.377] A lot has happened since then, and this review intends to capture such progress in the field. With both expert and novice in mind, we start by presenting the general principles underpinning the technique and discuss recent conceptual and methodological developments. We emphasise the increasing use of the technique as a non-invasive spectroscopic probe with intrinsic mass selectivity, as well as the concurrent use of neutron diffraction and first-principles computational materials modelling to guide and interpret experiments. To illustrate the state of the art, we discuss in detail a number of recent exemplars, chosen to highlight the use of electron-volt neutron spectroscopy across physics, chemistry, biology, and materials science. These include: hydrides and proton conductors for energy applications; protons, deuterons, and oxygen atoms in bulk water; aqueous protons confined in nanoporous silicas, carbon nanotubes, and graphene-related materials; hydrated water in proteins and DNA; and the uptake of molecular hydrogen by soft nanostructured media, promising materials for energy-storage applications. For the primary benefit of the novice, this last case study is presented in a pedagogical and question-driven fashion, in the hope that it will stimulate further work into uncharted territory by newcomers to the field. All along, we emphasise the increasing (and much-needed) synergy between experiments using electron-volt neutrons and contemporary condensed matter theory and materials modelling to compute and ultimately understand neutron-scattering observables, as well as their relation to materials properties not amenable to scrutiny using other experimental probes.